When innovation outpaces regulations: The legal challenges for direct‐to‐patient supply of investigational medicinal products. Issue 3 (13th October 2021) - Malone, Maeve; Ferguson, Pamela; Rogers, Amy; Mackenzie, Isla S.; Rorie, David A.; MacDonald, Thomas M.
Abstract : Aims: We profile the lack of specific regulation for direct‐to‐patient postal supply (DTP) of clinical trial medications (investigational medicinal products, IMPs) calling for increased efficiency of patient‐centred multi‐country remote clinical trials. Methods: Questionnaires emailed to 28 European Economic Area (EEA) Medical Product Licensing Authorities (MPLAs) and Swissmedic MPLA were analysed in 2019/2020. The questionnaire asked whether DTP of IMPs was legal, followed by comparative legal analysis profiling relevant national civil and criminal liability provisions in 30 European jurisdictions (including The Netherlands), finally summarising accessible COVID‐19‐related guidance in searches of 30 official MPLA websites in January 2021. Results: Twenty MPLAs responded. Twelve consented to response publication in 2021. DTP was not widely authorised, though different phrases were used to explain this. Our legal review of national laws in 29 EEA jurisdictions and Switzerland did not identify any specific sanctions for DTP of IMPs; however, we identified potential national civil and criminal liability provisions. Switzerland provides legal clarity where DTP of IMPs is conditionally legal. MPLA webpage searches for COVID‐19 guidance noted conditional acceptance by 19 MPLAs. Conclusions: Specific national legislation authorising DTP of IMPs, defining IMP categories, and conditions permitting the postage and delivery by courier in an EEA‐wide clinical trial, would support innovative patient‐centred research for multi‐country remote clinical trials. Despite it appearing more acceptable to do this between EU Member States, provided each EU MPLA and ethics board authorises it, temporary Covid‐19 restrictions in national Good Clinical Practice (GCP) guidance discourages innovative research into the safety and effectiveness of clinical trial medications.